Micro and Small Business Assistance through Accounting Training to Increase the Transaction Recording Capacity of Micro and Small Enterprises - Kambali, Muhammad; Permanasari, Lukita (PUDAK: Local Wisdom Community Journal, 2023)
The purpose of this Community Service is to provide understanding and capacity building of Micro and Small Enterprises in recording and bookkeeping transactions in their business. The use of accounting can be a very valuable tool for MSMEs in managing their business more effectively. Seeing the benefits generated by accounting, MSME actors should be aware that accounting is important for their companies. The use of accounting can support the progress of MSMEs, especially in financial terms. The facts in the field found that MSME actors in Domas village do not really understand the importance of recording transactions and financial reporting in the business activities carried out. Realizing this, the PKM Team assisted with the Accounting training method The training method was chosen with the consideration that this method was the most effective in realizing the objectives of PKM activities. The results of the mentoring stated that there was an increase in understanding and an increase in the ability to record business transactions carried out by showing the response of trainees which showed 85% of training participants stated that the mentoring activities were useful. The results of this assistance reinforce the importance of active participation in the campus world in developing and increasing the capacity of the business community through a series of PKM activities carried out as in other PKM results.